2012
DOI: 10.1119/1.3703517
|View full text |Cite
|
Sign up to set email alerts
|

Comparing large lecture mechanics curricula using the Force Concept Inventory: A five thousand student study

Abstract: The performance of over 5000 students in introductory calculus-based mechanics courses at the Georgia Institute of Technology was assessed using the Force Concept Inventory (FCI). Results from two different curricula were compared: a traditional mechanics curriculum and the Matter & Interactions (M&I) curriculum. Post-instruction FCI averages were significantly higher for the traditional curriculum than for the M&I curriculum; the differences between curricula persist after accounting for factors such as pre-i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 23 publications
(22 reference statements)
0
42
1
2
Order By: Relevance
“…28,40 At MSU, it is traditional to take this type of data for our introductory, calculus-based mechanics courses via the Force Motion Conceptual Evaluation (FMCE). 41 The results of this pre/post testing are often presented in the form of a normalized gain, which is the average increase in students' scores divided by the average increase that would have resulted if all students had perfect scores on the post-instruction test.…”
Section: Learning Outcomes a Conceptual Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…28,40 At MSU, it is traditional to take this type of data for our introductory, calculus-based mechanics courses via the Force Motion Conceptual Evaluation (FMCE). 41 The results of this pre/post testing are often presented in the form of a normalized gain, which is the average increase in students' scores divided by the average increase that would have resulted if all students had perfect scores on the post-instruction test.…”
Section: Learning Outcomes a Conceptual Learningmentioning
confidence: 99%
“…[26][27][28] While M&I was designed and developed before The Framework, the M&I curriculum and thus, P 3 , emphasizes a number of the critical aspects of The Framework. For example, P 3 is organized around core fundamental principles (conservation of momentum, energy, and angular momentum) meant to emphasize a first-principles approach to problem-solving, 29 which are akin to Core Ideas in The Framework.…”
mentioning
confidence: 99%
“…En las investigaciones de Henderson [20] el test se aplicó a una población de 2178 alumnos. Cabalero y otros [21] aplicaron FCI a 5000 estudiantes. Fagen, Crouch y Mazur [22] dicen que más de 500 profesores que aplicaron la metodología Peer Instruction administraron FCI en sus cursos para evaluar los resultados de los estudiantes.…”
Section: Introductionunclassified
“…Their scores on the Matter and Interactions Energy Test (MIET [50], administered 2009, 2010, and 2011) also increased, from 39% presemester to 76% postsemester. For comparison, Caballero et al found that gains of M&I students on the FCI are typically lower than those of equivalent students in a traditional course [51].…”
Section: B Previous Research Findingsmentioning
confidence: 99%